(untitled) (Journal of Academic Research, 2021)
In this article, we survey some elementary techniques for understanding the invariant theory of finite groups with emphasis on symmetric groups, and give an overview of a package for WxMaxima, called sym which contains tools for writing invariants in terms of many bases.